THE INFLUENCE OF THE SENSORY STIMULI ASPECTS FOR THE EFFICIENT USE OF URBAN SQUARES IN IRAQ - Ali, Omar Hussein; Ja’afar, Nor Haslina; Harun, Nor Zalina; Mat Sulaiman, Mohd Khairul Azhar (PLANNING MALAYSIA, 2022)
This study aims to examine the impact of user sensory stimuli aspects (comfort, passive and active engagements, relaxation, and discovery) on the efficient use of urban squares in Erbil, Iraq, through public interaction. A questionnaire survey (298 respondents) was employed to collect users’ opinions and was validated through expert interviews (13 interviewees) and field observations. PLS-SEM was used as the research method in this study to analyse the influence structure of the 298 respondents. The predicted model of the research can contribute to the body of knowledge among academics and practitioners. Findings revealed that the aspects of sensory stimuli have a significant influence on the efficient use of urban squares. For the efficient use of urban squares, comfort showed the greatest influence on social interaction.